2008
DOI: 10.1592/phco.28.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug Adherence Rates Among Patients with Seven Different Medical Conditions

Abstract: Study Objective-To compare drug adherence rates among patients with gout, hypercholesterolemia, hypertension, hypothyroidism, osteoporosis, seizure disorders, and type 2 diabetes mellitus by using a standardized approach. Design-Longitudinal study. Data Source-Health care claims data from 2001-2004.Patients-A total of 706,032 adults aged 18 years or older with at least one of the seven medical conditions and with incident use of drug therapy for that condition.Measurements and Main Results-Drug adherence was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
384
4
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(445 citation statements)
references
References 7 publications
30
384
4
12
Order By: Relevance
“…This hypothesis is consistent with: (1) the frequent association between several manifestations of nonadherence and smoking and alcohol habits: for instance, smoking and excessive alcohol consumption are independent predictors of low practice of self-monitoring of blood glucose in diabetic patients [39]; (2) the effect of young age on non-adherence in chronic diseases [7]; (3) the frequency of non-adherence in teenagers (an experimental study showed that adolescents and people in their twenties have more difficulties in finding similarities between them now and them in the future than older people [40]); (4) the fact that the level of maturity is associated with adherence to immunosuppressive drugs in adolescent and young adults following heart transplantation [41]; (5) data from fMRI studies, providing the evidence that the balance between frontal and limbic circuitries is relatively late maturing during the brain development from childhood to adult age [42,43]: it is tempting (even if hazardous) to see an explanation of a risk in teenagers, not only for addiction, but also for poor adherence; (6) the effect of social deprivation on non-adherence to medication [44]: a shorter temporal horizon was found to be associated to a lower income [38]; (7) the effect of education on adherence to medication and other health behaviours [45]: a stronger future orientation of women, who asked more frequently for BRCA1/2 screening and mammography, was seen in women who had higher levels of education [35]; and finally (8), this explanation may represent a common link leading to a clustering of preventive behaviours in some individuals, this concept of 'healthy adherer' explaining the puzzling observation that adherence to a placebo is associated with a decrease in mortality [46].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This hypothesis is consistent with: (1) the frequent association between several manifestations of nonadherence and smoking and alcohol habits: for instance, smoking and excessive alcohol consumption are independent predictors of low practice of self-monitoring of blood glucose in diabetic patients [39]; (2) the effect of young age on non-adherence in chronic diseases [7]; (3) the frequency of non-adherence in teenagers (an experimental study showed that adolescents and people in their twenties have more difficulties in finding similarities between them now and them in the future than older people [40]); (4) the fact that the level of maturity is associated with adherence to immunosuppressive drugs in adolescent and young adults following heart transplantation [41]; (5) data from fMRI studies, providing the evidence that the balance between frontal and limbic circuitries is relatively late maturing during the brain development from childhood to adult age [42,43]: it is tempting (even if hazardous) to see an explanation of a risk in teenagers, not only for addiction, but also for poor adherence; (6) the effect of social deprivation on non-adherence to medication [44]: a shorter temporal horizon was found to be associated to a lower income [38]; (7) the effect of education on adherence to medication and other health behaviours [45]: a stronger future orientation of women, who asked more frequently for BRCA1/2 screening and mammography, was seen in women who had higher levels of education [35]; and finally (8), this explanation may represent a common link leading to a clustering of preventive behaviours in some individuals, this concept of 'healthy adherer' explaining the puzzling observation that adherence to a placebo is associated with a decrease in mortality [46].…”
Section: Discussionsupporting
confidence: 80%
“…A recent study evaluated non-adherence in seven chronic diseases: hypertension, hypothyroidism, type 2 diabetes, seizure disorders, hypercholesterolaemia, osteoporosis and gout [7]. Sample sizes ranged from 4,984 patients for seizure disorders to 457,395 for hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this possibility suggests that our estimate of SU goal knowledge, although quite low, is likely higher than would be seen in a broader patient population. Our study also indicated high levels of medication adherence for both questionnaire responders and nonresponders relative to other recent studies (15,(37)(38)(39)(40)(41). The PDC values in our study are higher than in other studies, likely due to the high proportion of prevalent users in our cohort and the use of mailed prescriptions in the VA system.…”
Section: Discussionsupporting
confidence: 58%
“…Inadequate adherence to medications is unfortunately widespread across ages, health conditions, and medication regimens [10,[25][26][27]]. DiMatteo's [27] seminal review of over 500 adherence studies spanning multiple chronic conditions and medication classes reported an average medication nonadherence rate of 24.8 %.…”
Section: Defining Medication Adherence Behaviormentioning
confidence: 99%